Shared and distinct transcriptomic cell types across neocortical areas. (1st November 2018) - Tasic, Bosiljka; Yao, Zizhen; Graybuck, Lucas; Smith, Kimberly; Nguyen, Thuc; Bertagnolli, Darren; Goldy, Jeff; Garren, Emma; Economo, Michael; Viswanathan, Sarada; Penn, Osnat; Bakken, Trygve; et al.
Abstract The neocortex contains a multitude of cell types that are segregated into layers and functionally distinct areas. To investigate the diversity of cell types across the mouse neocortex, here we analysed 23, 822 cells from two areas at distant poles of the mouse neocortex: the primary visual cortex and the anterior lateral motor cortex. We define 133 transcriptomic cell types by deep, single-cell RNA sequencing. Nearly all types of GABA (γ-aminobutyric acid)-containing neurons are shared across both areas, whereas most types of glutamatergic neurons were found in one of the two areas. By combining single-cell RNA sequencing and retrograde labelling, we match transcriptomic types of glutamatergic neurons to their long-range projection specificity. Our study establishes a combined transcriptomic and projectional taxonomy of cortical cell types from functionally distinct areas of the adult mouse cortex. Single-cell transcriptomics of more than 20, 000 cells from two functionally distinct areas of the mouse neocortex identifies 133 transcriptomic types, and provides a foundation for understanding the diversity of cortical cell types.